Perceptual and Memorial Contributions to Developmental Prosopagnosia. Issue 2 (February 2017) - Ulrich, Philip I. N.; Wilkinson, David T.; Ferguson, Heather J.; Smith, Laura J.; Bindemann, Markus; Johnston, Robert A.; Schmalzl, Laura
Developmental prosopagnosia (DP) is commonly associated with the failure to properly perceive individuating facial properties, notably those conveying configural or holistic content. While this may indicate that the primary impairment is perceptual, it is conceivable that some cases of DP are instead caused by a memory impairment, with any perceptual complaint merely allied rather than causal. To investigate this possibility, we administered a battery of face perception tasks to 11 individuals who reported that their face recognition difficulties disrupt daily activity and who also performed poorly on two formal tests of face recognition. Group statistics identified, relative to age- and gender-matched controls, difficulties in apprehending global–local relations and the holistic properties of faces, and in matching across viewpoints, but these were mild in nature and were not consistently evident at the level of individual participants. Six of the 11 individuals failed to show any evidence of perceptual impairment. In the remaining five individuals, no single perceptual deficit, or combination of deficits, was necessary or sufficient for poor recognition performance. These data suggest that some cases of DP are better explained by a memorial rather than perceptual deficit, and highlight the relevance of the apperceptive/associative distinction more commonly applied to the allied syndrome of acquired prosopagnosia.